The Synthesis of (Magnetic) Crosslinked Enzyme Aggregates With Laccase, Cellulase, β-Galactosidase and Transglutaminase - Hojnik Podrepšek, Gordana; Knez, Željko; Leitgeb, Maja (Frontiers in Bioengineering and Biotechnology, 2022)
Immobilized enzymes have important aspects due to the fact that they possess higher stability, have the possibility to be easily removed from the reaction mixture, and are much easier to use when compared to free enzymes. In this research, the enzymes laccase, cellulase, β-galactosidase (β-gal), and transglutaminase (TGM) were immobilized by two different methods: crosslinked enzyme aggregates (CLEAs) and magnetic crosslinked enzyme aggregates (mCLEAs). The processes for CLEAs and mCLEAs preparation with different enzymes have been optimized, where the aim was to achieve the highest possible relative activity of the immobilized enzyme. The optimal conditions of the synthesis of CLEAs in mCLEAs are described, thus emphasizing the difference between the two types of immobilization based on different enzymes. This comparative study, which represents the synthesis of crosslinked enzyme aggregates using different enzymes, has not been performed so far. Moreover, the obtained activity of CLEAs and mCLEAs is presented, which is important for further use in different biocatalytic processes. Specifically, of a higher importance is the selection of enzymes involved in immobilization, as they belong to the three different most applicable enzymes (oxidoreductases, hydrolases, and transferases). The study confirmed that the resulting activity of the immobilized enzyme and the optimization of enzyme immobilization depended on the type of the enzyme. Moreover, the prepared CLEAs and mCLEAs were exposed to the supercritical carbon dioxide (scCO2) at different pressures to determine the effect of scCO2 on enzyme activity in immobilized form. Additionally, to demonstrate the reuse and stability of the immobilized enzyme, the stability and reusability tests of CLEAs and mCLEAs were performed. The catalytic performance of immobilized enzyme was tested, where the catalytic efficiency and long-term operational stability of mCLEAs were obviously superior to those of CLEAs. However, the higher activity observed for CLEAs compared to mCLEAs suggests a significant effect of magnetic nanoparticles in the stabilization of an enzyme crosslinked aggregate structure.